A retrospective study about incidental appendectomy during the laparoscopic treatment of intussusception - Tao Liu; Yibo Wu; Weijue Xu; Jiangbin Liu; Qingfeng Sheng; Zhibao Lv (Frontiers Media S.A., 2022)
PurposeWe aim to see incidental appendectomy (IA) was worth or not during the laparoscopic treatment of intussusception.MethodsThis study included forty-eight patients who underwent a laparoscopic procedure for idiopathic intussusception without intestinal resection between April 2014 and April 2021. The Chi-square or Fisher's exact tests for categorical variables and the Student t-test for continuous variables were used to analyze and compare patient characteristics.ResultsIA was performed on 63% (30/48) of patients after surgical reduction, while 18 (37%), did not. Patients who underwent IA had a higher total cost (16,618 ± 2,174 vs.14,301 ± 5,206, P = 0.036), and a longer mean operation duration (59 ± 19 vs.45 ± 21, P = 0.025). The distribution of the PO time, length of hospital stay, PCs, and RI did not differ significantly. The histopathological evaluation of the 30 resected appendices revealed five (17%) with signs of acute inflammation, 20 (66%) with chronic signs of inflammation, and five (17%) with inconspicuous appendices.ConclusionIA is linked to a longer average operation time and a higher total cost. There is insufficient evidence to recommend IA during laparoscopic intussusception treatment. The risks and benefits of IA need further study.